Aktivitas Antiparkinson Ekstrak dan Fraksi Buah Kemukus (Piper cubeba L.) pada Tikus Putih Galur Sprague Dawley - Damayanti, Kiki; Anas, Yance; Marlina, Windy; Nabila, Talcha; Irmawati, Putri (Jurnal Kefarmasian Indonesia, 2022)
Pathophysiologies underlying the Parkinson's disease is oxidative stress, can be treat with antioxidants from natural sources, including Piper cubeba L. Flavonoids are reported as antioxidants. This study aimed to analyse the flavonoids content and antiparkinson activity from the ethanolic extract of cubeb fruits (EECF), ethyl acetate fraction of ethanolic extract of cubeb fruits (EAFEECF), n-hexane fraction of ethanolic extract of cubeb fruits (NHFEECF). This research is an experimental study with a post test only control group design. Eighty four rats were divided into 14 groups. Group 1 is a normal group, group 2-3 are negative controls which were given aquadest and olive oil, respectively. Positive control groups, 4 and 5 were given levodopa 27 mg/kgBW and vitamin E 180 IU/kgBW, respectively. Group 6-14 were given EECF, EAFEECF, and NHFEECF at doses 150, 300, 600 mg/kgBW. Group 2-14 were induced with haloperidol 2 mg/kgBW intraperitoneally 45 minutes after administration of the material tests. The materials are given once a day for 7 days. The length of time the rats can hold on to the rotarod was tested on days 0, 4, 7, 11, 14. The curve showed the data on the survival time of rats on a rotarod versus time, then the AUC0-14 was calculated using the trapezoidal method. The AUC0-14 were analyzed using Mann Whitney test at 95%CI. The flavonoids content were analysed using TLC. The results showed that the EECF, EAFEECF, and NHFEECF contained flavonoids, and antiparkinson activity except for the NHFEECF at doses 150 and 600 mg/kgBW.